Research of the influence of the use of a feedback telecommunication system on the wire arc additive manufacturing process - Anikin, Pavlo (Technology audit and production reserves, 2023)
The object of the research is the possibilities of using a wireless communication system for feedback to improve the additive manufacturing process of a part using the arc welding technology with temperature control for heat propagation. The problem to be addressed includes determining the geometric properties, print topology, and temperature control regimes for the mentioned part. It also involves the installation of telecommunications sensors and cameras for temperature monitoring, conducting simulation calculations using ABAQUS software, and physical experiments. The results of the work include simulating the additive manufacturing process at necessary hierarchical system levels, considering specific requirements and obtaining the required geometric dimensions. Residual stresses have been analyzed, software-related heat propagation issues have been discussed, the influence of cooling on production quality has been verified, and optimal print parameters have been created. Additionally, the potential use of a feedback telecommunication system with telecommunication devices such as cameras and laser sensors for temperature control has been explored. The obtained data has been used for the possibility of generating an automated program for robot control during the additive manufacturing process. Based on the data obtained, residual stress values and defects in the produced samples were determined. A real experiment was conducted, and the results of the real experiment were compared and analyzed. The assessment of the impact of the feedback telecommunication system on the additive manufacturing process using arc welding with heat propagation control through cooling periods in practice allows for improved printing quality, technology of the produced part, cost reduction, and speeding up the production process.